Optimal depth selection of composite tubular-floor trusses based on cost estimation - AlHendi, Hashem; Mahmoud, Mohammad; Celikag, Murude (Sage Publications Inc, 2021)
The significance of this study initiates from the need to produce a selection guidance on the span range, span-to-depth ratio and scheme of the composite floor truss system to provide optimum performance and cost effectiveness for a particular application area. With this objective a parametric study was designed, based on three parallel chord trusses (Pratt, Howe, and Warren) using Rectangular Hollow Structural Shapes, a constant panel size of 2.5 m, four composite floor European-profiles and a range of load intensities. Hence, the span-to-depth ratios, R-S/D, and dead-to-live load ratios, R-DL/LL, were ranged from 3 to 27 and 0.84 to 3.22, respectively, for each truss type. The optimization was performed by using the design results of RFEM (2018) software for approximately 675 composite floor trusses with the objective of selecting optimal depth for each truss model. In addition, this paper attempts to introduce a cost function by considering the material, fabrication and painting costs and comparative figures allowing the design to be tailored with a focus on cost reduction. Accordingly, for all truss types, span-to-depth ratio of 9 to 12 with a span range of 7 to 23 m provides the most cost effective solution. Structural steel and the welding process are the two parameters that are found to have the highest impact on total cost.
Keywords: composite floor truss; cost function; Howe; optimization; Pratt; Warren